Dampak Polusi Udara terhadap Kesehatan dan Kesiapan Pertahanan Negara di Provinsi DKI Jakarta - Anatansyah Ayomi Anandari; Achmad Farid Wadjdi; Gentio Harsono (Journal on Education, 2024)
Air pollution in DKI Jakarta Province has reached alarming levels, threatening the health and quality of life of millions of residents and damaging the integrity of national defense preparedness. As the capital and center of Indonesian government, Jakarta plays an important role in the country's defense and security structure. This research was conducted to understand and evaluate the complex impacts of air pollution, which relate not only to public health but also to defense readiness. Through empirical data analysis, interviews with stakeholders, and the application of geospatial intelligence from satellite imagery, this research found various variables that correlate between air pollution, public health, and defense readiness. One of the main findings is that high levels of air pollution have a significant impact on public health conditions, which in turn can disrupt the country's defense readiness. Therefore, these results demonstrate the need for comprehensive and coordinated mitigation actions between various parties, including the provincial government, central government, and the military. These policies and actions should focus on protecting public health, preserving critical military infrastructure, and preparing the country to face additional challenges that may arise, such as climate change. In an increasingly interconnected and complex global context, this research highlights the urgency for a more holistic approach to addressing the problem of air pollution and its multifaceted impacts